2020
DOI: 10.1016/j.econmod.2019.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Culture and the capital–performance nexus in dual banking systems

Abstract: While recent surveys have taken a special interest in culture to explain the failure of existing regulation, empirical evidence on the role of culture in influencing the regulation-performance link is still largely unexplored. In this paper, we ask the following: Should regulators and policy makers make room for culture as an effective tool for a successful bank regulatory environment? We identify three proxies for cultural values derived from Hofstede (1980, 2001) and the World Values Survey and investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 47 publications
0
8
0
1
Order By: Relevance
“…Based on data availability of annual reports and access to databases, this study starts with a preliminary sample of 500 banks from 22 countries, and after applying several filtrations, the final sample included 395 banks from 19 different countries in the MENA region for 16 years between 1999 and 2014. Selecting banks for this study is supported by Bitar et al (2020), who stated that bank regulations and performance are influenced by culture. The sample includes countries located in the MENA region which are: Algeria; Bahrain; Egypt; Iran; Iraq; Israel; Jordan; Kuwait; Lebanon; Libya; Morocco; Oman; Palestine; Qatar; Saudi Arabia; Syria; Tunisia; United Arab Emirates; and Yemen.…”
Section: Sample and Data Collectionmentioning
confidence: 99%
“…Based on data availability of annual reports and access to databases, this study starts with a preliminary sample of 500 banks from 22 countries, and after applying several filtrations, the final sample included 395 banks from 19 different countries in the MENA region for 16 years between 1999 and 2014. Selecting banks for this study is supported by Bitar et al (2020), who stated that bank regulations and performance are influenced by culture. The sample includes countries located in the MENA region which are: Algeria; Bahrain; Egypt; Iran; Iraq; Israel; Jordan; Kuwait; Lebanon; Libya; Morocco; Oman; Palestine; Qatar; Saudi Arabia; Syria; Tunisia; United Arab Emirates; and Yemen.…”
Section: Sample and Data Collectionmentioning
confidence: 99%
“…Some of the studies concluded that culture can help to elaborate on the weak application of the regulatory system and deterrence of any potential financial turmoil. Bitar et al (2019) stated that bank regulations and performance are influenced by culture. For example, Islamic banks adopt a greater amount of ethical and proper guidelines and emphasize more to financial stability, equity and justice than conventional banks (Khan, 2010; Gheeraert, 2014).…”
Section: National Culture and Corporate Financial Decisionsmentioning
confidence: 99%
“…Likewise, national culture influences the country's financial system, financial institutions and economic mechanism (Boubakri et al , 2017). Moreover, the recent study by Bitar et al (2019) evidenced that culture has a significant impact on the capital-performance linkage between Islamic and conventional banks. Consequently, values and norms are powerful and effective tools to control the environment within the firms, banks and financial institutions and employees working in those institutions.…”
Section: National Culture and Corporate Financial Decisionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only when the narrative fits with the existing culture, it can be considered credible (Sherman and Roberto, 2020). Although culture is abstract, intangible and difficult to be quantified (Bitar et al, 2020), its influence to society is inherent. For example, culture serves as informal intuition for financial and strategic decision (Nash and Patel, 2019), and national culture has relation to the country financial sector (Kutan et al, 2020) or global financial crisis (Tran, 2020).…”
Section: Introductionmentioning
confidence: 99%